Communication Policy Elaboration: the Experience of the European Union - Карпчук, Наталія Петрівна; Karpchuk, Nataliia P. (University of Łodź, Department of Political Geography and Regional Studies ; Governmental Research Institute, Silesian Institute, 2013)
The article focuses on the stages of the EU Communication Policy elaboration since 2002 when the Commission made communication one of its strategic objectives to the tasks for 2010-2014.

Йдеться про етапи вироблення комунікаційної політики ЄС з 2002 р., коли Комісія визначила комунікацію однією із своїх стратегічних цілей, до завдань на 2010-2014 рр.
Вироблення комунікаційної політики: досвід Європейського Союзу
Keywords: Communication Policy; EU Communication Policy; European Commission; Action Plan; White Paper; комунікаційна політика; комунікаційна політика ЄС; Європейська комісія; План дій; Біла Книга